Temporal Trends in in-Hospital Bleeding and Transfusion in a Contemporary Canadian ST-Elevation Myocardial Infarction Patient Population - Das, Debraj (CJC Open, 2020)
BACKGROUND: Although ST-elevation myocardial infarction (STEMI) management has evolved substantially over the past decade, its effect on bleeding and transfusion rates are largely unknown in a contemporary population. METHODS: Our study cohort included patients 20 years of age or older who were hospitalized for STEMI between 2007 and 2016 across all Canadian provinces, except Quebec. Unadjusted rates of bleeding and of transfusion during STEMI episodes were calculated overall and for each province according to fiscal year. Patients were stratified into 4 groups according to their bleeding/transfusion. Characteristics, treatment, and outcomes were compared between groups. Multivariate logistic regression modelling was used to assess the association between bleeding and transfusion on in-hospital mortality. RESULTS: Using 108,832 STEMI episodes, rates of in-hospital bleeding and transfusion declined between 2007 and 2016 from 3.9% to 2.8% (P < 0.0001) and 4.7% to 3.8% (P < 0.0001), respectively. However, variation in bleeding and transfusion rates were observed across Canadian provinces. Patients with bleeding or transfusion, were older, female, and had more comorbidities. Compared with patients who did not bleed or receive a transfusion, individuals who bled, were transfused, or bled and were transfused, had higher in-hospital mortality (18.6%, 30.3%, and 30.4%, respectively [P < 0.0001]). The association remained after adjustment: bleeding (odds ratio [OR], 2.0; 95% confidence interval [CI], 1.8-2.4), transfusion (OR, 4.4; 95% CI, 3.9-4.9), and bleeding and transfusion (OR, 3.8; 95% CI, 3.2-4.6). CONCLUSIONS: The proportion of Canadian STEMI patients who experienced in-hospital bleeding and transfusion has decreased over the past 9 years. However, patients with bleed or transfusion remain at higher risk of adverse outcomes.